First report of Atherigona reversura Villeneuve, 1936 (Diptera, Muscidae) in Uruguay - Remedios De León, Mónica (2021)
We present the first record of Atherigona reversura Villeneuve, 1936 in Uruguay, from Pando, Canelones department a rural area used for livestock. Atherigona reversura, this muscid, commonly known as shoot-fly, is a significant pest of cereal crops throughout the Old World tropics and subtropics and its main host is Bermudagrass, Cynodon dactylon L.Pers., an exotic species which is widely distributed in South America and in Uruguay and has economic value as forage for livestock and is damaged by the feeding of A. reversura larvae.